Biomarkers of central and peripheral inflammation mediate the association between HIV and depressive symptoms - Arish Mudra Rakshasa-Loots; Nicholas Bakewell; David J. Sharp; Magnus Gisslén; Henrik Zetterberg; Jasmini Alagaratnam; Ferdinand W. N. M. Wit; Neeltje A. Kootstra; Alan Winston; Peter Reiss; Caroline A. Sabin; Jaime H. Vera; et al. (Translational Psychiatry, 2023)
Abstract People living with HIV are at increased risk for depression, though the underlying mechanisms for this are unclear. In the general population, depression is associated with peripheral and central inflammation. Given this, and since HIV infection elicits inflammation, we hypothesised that peripheral and central inflammatory biomarkers would at least partly mediate the association between HIV and depressive symptoms. People living with HIV (n = 125) and without HIV (n = 79) from the COmorBidity in Relation to AIDS (COBRA) cohort were included in this study. Participants living with and without HIV had similar baseline characteristics. All participants living with HIV were on antiretroviral therapy and were virally suppressed. Plasma, CSF, and brain MR spectroscopy (MRS) biomarkers were measured. Using logistic regression models adjusted for sociodemographic factors, we found that participants with HIV were more likely to have Any Depressive Symptoms (Patient Health Questionnaire [PHQ-9] score >4) (odds ratio [95% confidence interval] 3.27 [1.46, 8.09]). We then sequentially adjusted the models for each biomarker separately to determine the mediating role of each biomarker, with a >10% reduction in OR considered as evidence of potential mediation. Of the biomarkers analysed, MIG (−15.0%) and TNF-α (−11.4%) in plasma and MIP1-α (−21.0%) and IL-6 (−18.0%) in CSF mediated the association between HIV and depressive symptoms in this sample. None of the other soluble or neuroimaging biomarkers substantially mediated this association. Our findings suggest that certain biomarkers of central and peripheral inflammation may at least partly mediate the relationship between HIV and depressive symptoms.